Evaluation of Antidiabetic Drug Selection and Dosage Appropriateness in Hospitalized Type 2 Diabetes Mellitus Patients at RSU Royal Prima Medan. January-June 2024 - Purba, Helprida GM; Yunus, Muhammad; Ginting, Astriani Natalia Br (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease that requires appropriate drug management to achieve optimal blood glucose control. Appropriateness of drug and dose is essential to ensure the effectiveness of therapy. while cost-effectiveness analysis is needed to assess the efficiency of resource use in its management. This study aims to assess the appropriateness of the use of drugs and doses of type 2 antidiabetics based on PERKENI 2021 clinical guidelines and analyze the cost-effectiveness of therapy in hospitalized patients. This study used a retrospective descriptive method with a cross-sectional approach. The research was conducted in January-February 2025 using purposive sampling technique.The result of the 43 patients. the majority were female (55.8%) and aged 56-65 years (48.8%). The suitability of drug use in accordance with PERKENI 2021 reached 100%. but there was a dose discrepancy of 1.36%. namely the drug sitagliptin. Based on ACER and ICER parameters. the most cost-effective monotherapy is Glimepirid with an effectiveness value of 100%. an ACER value of IDR 83.886.43. while the most cost-effective combination therapy is Pioglitazon + metformin with an effectiveness value of 100%. an ACER value of IDR 100.639.21 and an ICER value of IDR 76.734.39 and IDR 13.317.37. Most of the therapies are in accordance with the PERKENI 2021 guidelines. but dosage accuracy still needs to be improved.